STRATEGI PEMASARAN KRIPIK BALADO PADA USAHA KERIPIK PUTI PILIANG DI KABUPATEN PADANG PARIAMAN - Mukti Diapepin; Retno Larasandi (Jurnal Public Administration, Business and Rural Development Planning, 2019)
Along with the increasingly globalized era of modernization in which small industries began to develop, both through increased technology and increased productivity so as to tighten competition among small business owners. Thus the small industry of cassava chips is experiencing competition so it is necessary to have business marketing strategies in business development. The strength contained in the business, which is analyzed is a supporting factor marketing in this business is in the field of service, namely delivering orders to consumers / customers directly. Previous strategies / other strengths owned by the Piliang chips business are: excellence recognized by customers (taste, packaging, and health), having regular customers. (supermarkets and stalls), the best quality raw materials, give bonuses for purchases starting from 3kg. This business has problems with the product, low production results making it difficult to meet the demands of consumers in large numbers and places that are difficult to reach by consumers and therefore need to look for a solution in order to continue to exist and compete with other products.